2006
DOI: 10.1016/j.jasms.2006.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Protein identification via surface-induced dissociation in an FT-ICR mass spectrometer and a patchwork sequencing approach

Abstract: Surface-induced dissociation (SID) and collision-induced dissociation (CID) are ion activation techniques based on energetic collisions with a surface or gas molecule, respectively. One noticeable difference between CID and SID is that SID does not require a collision gas for ion activation and is, therefore, directly compatible with the high vacuum requirement of Fourier transform ion cyclotron resonance (FT-ICR) mass spectrometers. Eliminating the introduction of collision gas into the ICR cell for collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…These qualifiers, consisting mainly of a 2 , b 2 , y 1 , y 2 , and internal and immonium type ions, provide additional restraints during database searching that help ensure the correct peptide is identified. Fernandez et al [87] demonstrated that SID in an FT-ICR yielded a large number of these qualifier ions, improving the statistical significance of database searches. In addition, SID conducted on a diamond surface provided improved sequence coverage over SORI-CID resulting from the accessibility of both fast and slow dissociation pathways not readily accessible by CID.…”
Section: The Role Of Sid In Developing the Mobile Proton Model And Elmentioning
confidence: 99%
“…These qualifiers, consisting mainly of a 2 , b 2 , y 1 , y 2 , and internal and immonium type ions, provide additional restraints during database searching that help ensure the correct peptide is identified. Fernandez et al [87] demonstrated that SID in an FT-ICR yielded a large number of these qualifier ions, improving the statistical significance of database searches. In addition, SID conducted on a diamond surface provided improved sequence coverage over SORI-CID resulting from the accessibility of both fast and slow dissociation pathways not readily accessible by CID.…”
Section: The Role Of Sid In Developing the Mobile Proton Model And Elmentioning
confidence: 99%
“…7,15 The use of these easy-to-prepare surfaces has persisted, although several other surface types have been utilized. 1624 These SAMs provide a large effective mass for collision of projectile ions, the fluorocarbon chains are relatively rigid so that they don’t severely dampen the energy of the colliding projectile, and the fluorocarbon resists facile electron transfer to the incoming ions. Surface targets, in contrast to the typical gaseous targets such as Ar that are used for the more common activation method collision-induced dissociation (CID), have proven to be exceptionally useful for the characterization of protein complex quaternary structure.…”
Section: Introduction To Surface-induced Dissociationmentioning
confidence: 99%
“…Because Mg 2+ can stabilize protein and RNP complexes [17] and create structures that are difficult for CID to break apart, SID was used to dissociate RNPs in the presence of Mg 2+ . SID deposits high energy into the ions through a single collision event with a surface [18] to reveal dissociation pathways with high energy barriers and high rates, which are likely for RNP disassembly. In tandem with IM, SID can be employed to dissociate a putative RNP complex, thereby confirming its identity and revealing substructures.…”
mentioning
confidence: 99%